Immune pathogenesis of heparin-induced thrombocytopenia - Khandelwal, Sanjay; Arepally, Gowthami M. (Thrombosis and Haemostasis, 2016)
The immune response to heparin is one of the most common drug-induced allergies, and yet, atypical for a drug hypersensitivity reaction. Whereas most drug-induced allergies are rare, idiosyncratic and lifelong, the allergic response to heparin is common, predictable in certain clinical settings and transient. Advances in the last decade with regards to structural characterisation of the PF4/heparin antigenic complex, contributions of innate immunity and development of animal models have provided insights into the distinctive features of the HIT immune response. Recent descriptions of the crystal structure of the PF4/heparin complex, alongside other biophysical studies, have clarified the structural requirements for immunogenicity and heparin-dependency of antibody formation. Studies of interactions of PF4 with bacterial cell walls as well as epidemiologic associations of anti-PF4/heparin antibody formation and infection suggest a role for immune priming and explain the rapid evolution of an isotype-switched immune response in sensitised patients. Murine models have greatly facilitated investigations of cellular basis of the HIT response and identified a major role for T-cells and marginal zone B-cells, but key findings have yet to be validated in human disease. This chapter will summarise recent investigations of the HIT immune response in the context of major pathways of immune activation and identify areas of uncertainty.
Keywords: Heparin-induced thrombocytopenia; platelet factor 4; heparin; murine models